Torands revisited: Metal sequestration and self-assembly of cyclo-2,9-tris-1,10-phenanthroline hexaaza macrocycles - Schwab, Matthias Georg; Takase, Masayoshi; Mavrinsky, Alexey; Pisula, Wojciech; Feng, Xinliang; Gamez, Jose A.; Thiel, Walter; Mali, Kunal S.; De Feyter, Steven; Muellen, Klaus (Chemistry - A European Journal, 2015)
A series of novel toroidal cyclo-2,9-tris-1,10-phenanthroline macrocycles with an unusual hexaaza cavity are reported. Nickel-mediated Yamamoto aryl-aryl coupling was found to be a versatile tool for the cyclotrimerization of functionalized 1,10-phenathroline precursors. Due to the now improved processability, both liquid-crystalline behavior in the bulk phase and two-dimensional self-assembly at the molecular level could be studied, for the first time, for a torand system. The macrocycles exhibited a strong affinity for the complexation of different metal cations, as evidenced by MALDI-TOF analysis and spectroscopic methods. Experimental results were correlated to an extensive computational study of the cyclo-2,9-tris-1,10-phenanthroline cavity and its binding mode for metal cations. Due to the combination of several interesting features, toroidal macrocycles may find future applications in the field of ion and charge transport through molecular channels, as well as for chemical sensing and molecular writing in surface-confined monolayers under STM conditions.
CRIS-Team Scopus Importer:2023-03-20
Keywords: liquid crystals; macrocycles; phenanthrolines; scanning probe microscopy; self-assembly